Dark and magical places : the neuroscience of navigation - Kemp, Christopher (W. W. Norton & Company, 2022)
"An illuminating examination of how the brain helps us to understand and navigate space-and why, sometimes, it doesn't work the way it should. Navigation is one of the most complex tasks our brains perform. And we do it countless times a day-as we drive across town to the airport, or traverse the maze of a supermarket, or walk within our own homes. But why is it that some people are lost on their own street and others can seamlessly navigate a new city after visiting it once? Fueled by his own spatial shortcomings, Christopher Kemp describes the brain regions that orient us in space and the specialized neurons-place cells and grid cells-that do it. He explains how the brain plans routes, recognizes landmarks, and makes sure we leave a room through a door instead of a painting. Along the way, he meets the scientists trying to understand the mental maps of modern humans, and Neanderthals, and lost people everywhere. Dark and Magical Places is an informed and entertaining journey into the mysteries of the mind"--